Letter (copy) : Organising leaflet: unemployed. Scottish Ambulance Unit in Spain - Tewson, Vincent
042-0115-001 HVT/FC/EK/1514. Secretary's. 1st September, 1937. Mr. W. Elger, The Scottish Trades Union Congress, 55, Elmbank Crescent, GLASGOW. Dear Mr. Elger, ORGANISING LEAFLET - UNEMPLOYED. I received your telegram yesterday and, in accordance with your request, sent a sample of our organising leaflet for Unemployed Associations to Mr. Shanks. I also received your letter this morning, and am enclosing herewith samples of the leaflet, the price of which is 1/6 per thousand. (subsidised price) The back of the leaflet is left blank to enable Associations to print their own propaganda matter, or notices of meetings. SCOTTISH AMBULANCE UNIT IN SPAIN I am enclosing herewith copy of a letter which was sent to Sir Daniel Stevenson on the 26th August. Actually we find that the sum of £2,200 has been granted to the Scottish Ambulance Unit against a sum of £1,900 to the Spanish Medical Aid Committee. Yours sincerely, Assistant Secretary. Unemployed Leaflets. Copy of letter. 292/946/42/115